Social independence evaluation index for Japanese patients with childhood-onset chronic diseases - Inoue, Yuzaburo; Umebayashi, Hiroaki; Matsui, Toshihiro; Nishiyama, Susumu; Sakurai, Ikuho; Maru, Mitsue; Takeda, Tetsuro; Tanigawa, Koji; Miyamae, Takako (Frontiers in Pediatrics, 2022)
Introduction This study established an independent evaluation index for patients with childhood-onset chronic diseases in Japan. Methods From November to December 2020, three Delphi rounds were conducted. Thirty-nine participants completed at least one survey. We asked them about targets of social independence for 10 types of activities (education/labor/finance/acquisition of necessities/housing/transportation/leisure/social relationship/intimate relationships/sexuality). The Delphi technique was to be repeated until a consensus of over 80% of participants was reached. Results The targets chosen for measuring independence in patients with childhood-onset chronic diseases were as follows: “Graduation from high school,” “Labor for livelihood (including temporary turnover),” “Financially independent (including temporary turnover, excluding students),” “Buy or rent a house and buy the daily necessities and get the public services you need to live,” “Do housework alone,” “Plan alone and use transportation to get around,” “Participate in play/recreation/leisure activities on own initiative,” “Engage in relationships with other people outside of a limited environment (home, school, office, hospital, etc.),” “Create and maintain intimate or romantic relationships between individuals (couples, lovers, sexual partners),” and “Use or know how to use contraceptives and how to prevent sexually transmitted diseases.” Conclusions We established an independent evaluation index for patients with childhood-onset chronic diseases in Japan through a three-round Delphi process. The assessment of social independence using our independent evaluation index may help plan for and provide appropriate support and assistance to these patients.